The relationship between medication compliance and therapy outcome in outpatients patient with type 2 diabetes mellitus at PKU Muhammadiyah Gombong Hospital: The Relationship Between Medication Compliance And Therapy Outcome In Outpatients Patient With Type 2 Diabetes Mellitus At PKU Muhammadiyah Gombong Hospital - Sarwoko, Sarwoko; Widiastuti, Tri Cahyani; Rahmatulloh, Wahyu; Sodik, Anwar (JFL : Jurnal Farmasi Lampung, 2025)
Diabetes is a metabolic condition characterized by chronic hyperglycemia due to decreased insulin synthesis or insulin resistance. The prevalence of type 2 diabetes mellitus in Central Java has increased by 0.5%. The aim of this study was to determine the relationship between medication adherence and therapeutic outcomes in outpatients with type 2 diabetes mellitus at PKU Muhammadiyah Gombong Hospital. The study used a non-experimental method with an analytical and descriptive cross-sectional design and a prospective approach (observing respondent adherence) for 3 months of treatment. The level of adherence to drug therapy in type 2 diabetes mellitus patients at the Outpatient Installation of PKU Muhammadiyah Gombong Hospital was dominated by the category of moderately adherent (70 patients) , non-adherent (28 patients) , and adherent (2 patients) . The results of the Spearman rho statistical test indicated a p-value of 0.000 (p<0.05) for both outcome parameters (HbA1c and GDS). The correlation between adherence scores and HbA1c was -0.830 (a very strong correlation), while the correlation with GDS was -0.463 (a moderately strong correlation). There was a significant correlation between medication adherence and therapeutic outcomes in patients with type 2 diabetes mellitus at the Outpatient Unit of PKU Muhammadiyah Gombong Hospital.